UPAYA MENINGKATKAN KEMAMPUAN GURU DALAM MENGEFEKTIFKAN PEMBELAJARAN MELALUI SUPERVISI KELAS DI SD - Eriyani Eriyani (Manajer Pendididikan, 2017)
The purpose of this study was to determine ability ofteachers in streamline of learning through the teacher professional founding program and classroom supervision in SD Negeri 04 Kepahiang in the academic years 2015/2016. This study is the research action. The analysis showed that was a determine ability in the effective management of learning in the first cycle which scored A 33.3% scored B at 0% and the scored C by 66.7%, in the second cycle which scored A 44.44% scored B of 22.2% and scored C 22.2%, while the third cycle which scored A 44% scored B 33% and the scored C 22%. It can be concluded that through the teacher professional supervisor program and classroom supervision was determine ability of teacher to streamline themanagement of learning.